Comunicar Design e Cultura - Maria Jorge Fernandes Ventura Ferreira (2021)
This master thesis is based on the creation of a proposal for a communication plan for 'Clink', a project used as a case study, in the scope of design and culture. The investigation begins with the general themes of communication and marketing, proceeding with an analysis of both with special incidence in the scope of culture and the arts, in order to gather the necessary information to carry out the communication plan. Along with the developed research, the adopted methodology intends to understand the current communication trends in the field of design, culture and the arts, themes that support the project in question.